2013
DOI: 10.7763/ijfcc.2013.v2.137
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Safety Analysis Techniques for Safety Critical Systems

Abstract: Abstract-This paper is mainly focused on the study of the techniques available for the safety analysis of critical systems. It is never possible to build a completely safe system. There is a possibility to bring the behavior of these systems within acceptable limits. For safety evaluation of such systems both formal and informal techniques are available. Both techniques have their own prospects and consequences. Informal techniques are simpler to learn and easier to interpret and have more space for creativity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…They go on to conclude that use of only one analysis technique is insufficient, and suggest combined usage of methods is important in safety analysis of critical systems. Haider and Nadeem (2013) detailed the informal and formal techniques which are available for the safety analysis of critical systems. Their study found that a combination of formal and informal techniques can reap the benefits of each method; that using the input of informal techniques into a formal technique can narrow the scope of the minimal critical set.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They go on to conclude that use of only one analysis technique is insufficient, and suggest combined usage of methods is important in safety analysis of critical systems. Haider and Nadeem (2013) detailed the informal and formal techniques which are available for the safety analysis of critical systems. Their study found that a combination of formal and informal techniques can reap the benefits of each method; that using the input of informal techniques into a formal technique can narrow the scope of the minimal critical set.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bozzano (2010) [15] contributed to the safety assessment of critical systems with a book focused on techniques and methods for dependability, reliability, and safety assessment [15]. Illiashenko (2012) [14] [16]. Early researches described limited experimental concepts.…”
Section: Introductionmentioning
confidence: 99%